Research on the path evolution and policy of China’s agricultural products export to countries along the Belt and Road - Dongsheng Liao; Xi Chen (Journal of Frontier in Economic and Management Research, 2025)
The purpose of this paper is to examine the joint effect of China on the influencing factors of agricultural products export along the Belt and Road (B&R) and the evolution of its path. We selected 50 countries along the B&R as research samples. By integrating the influencing factors of export scale and introducing fuzzy set qualitative comparative analysis (fsQCA). The results show that: (1) population size, economic scale, trade facilitation, institutional environment and geographical distance are not the necessary conditions for the path of China’s agricultural export trade to countries along the B&R. (2) after comparing the analysis results in 2013 and 2019, it is found that the high path of China’s agricultural export trade to the B&R is relatively stable. However, the negative impact of geographical distance on one of the paths is significantly weakened, while the positive effect of the level of trade facilitation is gradually significant. (3) the not-high path of China’s agricultural export trade to countries along the B&R is unstable and more complex. The weak market demand drive caused by the small economic scale and small population size is still an essential factor in the less path. Finally, based on the above research conclusions, We put forward policy implications for the sustainable development of China’s agricultural export trade to countries along the B&R.